The Wealth of Maritime Country and the Welfare of Coastal People: Between Imagination and Reality - Setiawan, Rahmad Fahreza; Wahyu Akbar, Wahyu Akbar (Journal of World Trade Studies, 2024)
Indonesia is dubbed a maritime country because its water area is larger than its land area and consists of many islands. Indonesia's natural resources on land alone are already abundant, let alone the vast water areas that hold even more wealth of resources that can be utilized. However, do dreams and facts about the richness of marine resources correlate? This article discusses the welfare of coastal communities, opportunities, and challenges in optimizing the utilization of marine resources. Nearly 40 million people live in coastal areas, raising the question of why they have a low level of welfare despite this great potential. This article outlines the factors causing the low welfare of coastal communities and the associated challenges. Indonesia has a great opportunity to improve the welfare of coastal communities and the Indonesian economy through proper and effective management of marine resources if the challenges are overcome. With this article, it is hoped that readers can understand and actively contribute to maximizing the utilization of marine resources for every element of society. Library Research is the research method used with a descriptive approach to produce outputs that are easily understood by various groups. This article shows the vast potential and opportunities that marine resources hold for society and the economy in Indonesia if utilized effectively and efficiently.